Isoetes shangrilaensis, a new species of Isoetes from Hengduan mountain region of Shangri-la, Yunnan - Li, Xiang; Huang, Yuqian; Dai, Xiaokang; Liu, Xing (Phytotaxa, 2019)
Isoetes shangrilaensis is recognized as a new species in Shangri-la and compared with Isoetes hypsophila, another species in the Hengduan Mountain Region. Spore sizes and ornamentations are useful to distinguish these two species. Isoetes shangrilaensis has tuberculate to rugulate megaspores and echinate to cristate microspores while Isoetes hypsophila has laevigate megaspores and bacculate to rugulate microspores. One nuclear and three chloroplast DNA sequences were used to infer the phylogenetic relationships of I. shangrilaensis, I. hypsophila and two other basic diploid Isoetes species (Isoetes taiwanensis and I. yunguiensis) in China. The phylogenetic tree showed a distinct separation between these two species: I. shangrilaensis was more closely related to other basic diploid species in China whereas I. hypsophila was distantly related. The delineation of Isoetes in this region can contribute to a better understanding of its phylogeny.